Designing a Competency-Based Recruitment Plan for Human Resource Manager in PT. Produksi Dari Hati (Journal of Business and Management, 2021)
Recruitment plan is the planning of a process aimed at selecting the best candidate for a job/position. Competency-based human resource management is a coherent and interrelated set of human resource management practices in all its areas: from the individual entering the organization, through effective functioning, development, until leaving the organization. PT Produksi Dari Hati (PT PDH) is a startup company in Indonesia that has been engaged in the film and creative industries since 2019. The company aims to expand its business and recruit new talents to help the company achieve these goals. This study aims to define the core, functional, and managerial competencies in accordance with the company's strategic objectives as initial capital for designing HR policies and practices. The results of these processes will be used as basic data in making recruitment plans for HR managers in PT PDH. This study uses a competency-based recruitment plan for HR managers. The research data was collected using triangular data as the main method, which was obtained from document analysis, literature review, and interviews with the Co-Founder of the company. Data were analyzed using Spencer's theory as a guide to determine competencies, references to the world economic forum competency classification as a guide to current competencies, and Gary Dessler's theory as a reference for creating recruitment plans. The result of this research is the soft competencies dictionary (core, functional, managerial competencies) for PT Produksi Dari Hati, and hard competencies, job analysis and recruitment plans for HR manager in PT PDH.Keywords: Recruitment Plan, Competency-Based Human Resource Management, Startup Company, HR Manager